2012
DOI: 10.4209/aaqr.2012.03.0065
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Two-Stage Scrubbing Technology for Odor Control of Kitchen Waste Composting

Abstract: The odors associated with kitchen waste composting for recycle and reuse, which arise as a consequence of the volatilization of compounds contained within such waste and those formed during decomposition, are a key concern with regard to sustainable kitchen waste treatment and disposal. The aim of this study was to investigate the main composition of the odorous gases from kitchen waste composting, and to develop a novel two-stage oxidative-reductive wet scrubbing technology for effective control of these. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…These compounds were widely and commonly found in the preceding studies that monitored the ambient air qualities of waste disposal and landfill sites (Allen et al, 1997;Zou et al, 2003). A strong correlation between the concentrations of odor and two sulfur-containing compounds, hydrogen sulfide and mercaptans, was found in our preceding study as well (Chen et al, 2012).…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…These compounds were widely and commonly found in the preceding studies that monitored the ambient air qualities of waste disposal and landfill sites (Allen et al, 1997;Zou et al, 2003). A strong correlation between the concentrations of odor and two sulfur-containing compounds, hydrogen sulfide and mercaptans, was found in our preceding study as well (Chen et al, 2012).…”
Section: Introductionmentioning
confidence: 68%
“…The early published study has indicated the occurrence of strong pH variations in both scrubbers when this twostage chemical wet scrubbing technology was operated as a batch system in bench-scale (Chen et al, 2012). As shown in Fig.…”
Section: Ph Variations In Two Scrubbersmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] In the flavour and fragrance industry, H 2 S and CH 3 SH find beneficial applications in the flavouring of foods such as meat or coffee products. [4] These sulfur compounds may contribute to toilet, [5] kitchen [6] or breath [7] malodours, and thus for homecare products, they should be prevented from being formed or should be counteracted with a perfume.…”
Section: Introductionmentioning
confidence: 99%